Deposition of Cross-Linked Dopamine and Polyethylenimine on Polypropylene Separators via One-Step Soaking Method for Li-S Batteries. Issue 4 (16th February 2019) - Meng, Zhaoting; Huang, Yudai; Li, Jing; Yang, Ruina; Wang, Xingchao; Guo, Yong; Liu, Zhenjie; Xi, Murong; Su, Wenqi; Wang, Lei
Abstract : A facile and simple strategy to modify polypropylene (PP) separators with dopamine (DA) and polyethylenimine (PEI) has been proposed. The cross-linked DA-PEI nanoparticles can be adsorbed to the PP separator by the quinonyl groups of DA efficiently. The electrolyte wettability of the modified separator is obviously improved. The Li-S battery with the modified separator delivers a high cycling capacity and rate capacity. The specific capacity of Li-S battery with A1P3 separator is 1033.4 mA h g −1 and stabilizes at 470.8 mA h g −1 at 0.2 C after 100 cycles. And its rate capacity at 0.2 C, 0.5 C, 1 C, and 2 C is 1016.5 mA h g −1, 754.6 mA h g −1, 676.2 mA h g −1, and 463.6 mA h g −1, respectively. The outstanding electrochemical performance could be ascribed to that the polar deposited layer, which not only alleviates the shuttle effect by physical blocking and electrostatic interactions, but also facilitates Li + ions migration by the improved electrolyte wettability.